Effects of Orientation on the Properties of Fan Palm Fibre Reinforced Sheet - Adeleke, O. A.; Yinusa, B.; Azeez, M. A.; Arisoyin, A. G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
In this research, the effect of orientation of the strength of fan palm fibre reinforced sheets was investigated. The material used was fan palm fibre whose length varies from 0.8 to 1.7m with an average bulk density of 1.133g/cm3, specific gravity of 0.46 and Moisture Content (MC) of 7.40%. And the mould used was a wooden mould of 300×300×9 mm. The fibre was soaked in both water and cement slurry for 24 hours and 7 days. Soil sieve analysis was carried out using ASTM standard and curing was done for 28 days. The percentage of fibre in the sampled reinforce sheet was between 1-3% at various orientations (0, 30, 60° and 2D). The properties examined were Water Absorption (WA), Compressive Strength (CS) and Flexural Strength (FS). Data analysis was done using Response Surface Methodology (RSM). The results showed that the reinforced sheets with long fibre of 1, 2 and 3% have WA of 5.76, 3.72 and 5.05% respectively. While those with short fibre of 1, 2 and 3% have 6.87, 7.36 and 7.75% respectively. The CS of the reinforced sheets of 1, 2 and 3% fibre at 0, 30, and 600 orientations were 6.9568, 8.0779, 7.2330; 3.2870, 6.6764, 7.355; and 3.0592, 5.3215, 3.9090 N/mm2 respectively and the FS results were also observed. The CS and FS of reinforced sheets at 00 and 300 fibre orientations seems to be the best.